School for children - (:unkn) unknown (Coy C. Carpenter Library, 2009)
Info from 13:292; Meads, box 9, Graylyn folder; Katherine Davis Oral History #61:26
This photograph is believed to be workers with children at the Graylyn Exceptional School for Children which operated from approximately 1958 to 1972 at the former home of Bowman Gray, Sr. and his wife, Nathalie Bernard Gray, known as Graylyn Estate.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth